Untangling the transmission dynamics of primary and secondary vectors of Trypanosoma cruzi in Colombia: Parasite infection, feeding sources and discrete typing units (2023)
Background: Trypanosoma cruzi is the causative agent of Chagas disease. Due to its genetic diversity has been classified into six Discrete Typing Units (DTUs) in association with transmission cycles. In Colombia, natural T. cruzi infection has been detected in 15 triatomine species. There is scarce information regarding the infection rates, DTUs and feeding preferences of secondary vectors. Therefore, the aim of this study was to determine T. cruzi infection rates, parasite DTU, ecotopes, insect stages, geographical location and bug feeding preferences across six different triatomine species. Methods: A total of 245 insects were collected in seven departments of Colombia. We conducted molecular detection and genotyping of T. cruzi with subsequent identification of food sources. The frequency of infection, DTUs, TcI genotypes and feeding sources were plotted across the six species studied. A logistic regression model risk was estimated with insects positive for T. cruzi according to demographic and eco-epidemiological characteristics. Results: We collected 85 specimens of Panstrongylus geniculatus, 77 Rhodnius prolixus, 37 R. pallescens, 34 Triatoma maculata, 8 R. pictipes and 4 T. dimidiata. The overall T. cruzi infection rate was 61.2% and presented statistical associations with the departments Meta (OR: 2.65; 95% CI: 1.69-4.17) and Guajira (OR: 2.13; 95% CI: 1.16-3.94); peridomestic ecotope (OR: 2.52: 95% CI: 1.62-3.93); the vector species P. geniculatus (OR: 2.40; 95% CI: 1.51-3.82) and T. maculata (OR: 2.09; 95% CI: 1.02-4.29); females (OR: 2.05; 95% CI: 1.39-3.04) and feeding on opossum (OR: 3.15; 95% CI: 1.85-11.69) and human blood (OR: 1.55; 95% CI: 1.07-2.24). Regarding the DTUs, we observed TcI (67.3%), TcII (6.7%), TcIII (8.7%), TcIV (4.0%) and TcV (6.0%). Across the samples typed as TcI, we detected TcIDom (19%) and sylvatic TcI (75%). The frequencies of feeding sources were 59.4% (human blood); 11.2% (hen); 9.6% (bat); 5.6% (opossum); 5.1% (mouse); 4.1% (dog); 3.0% (rodent); 1.0% (armadillo); and 1.0% (cow). Conclusions: New scenarios of T. cruzi transmission caused by secondary and sylvatic vectors are considered. The findings of sylvatic DTUs from bugs collected in domestic and peridomestic ecotopes confirms the emerging transmission scenarios in Colombia. © 2016 The Author(s).